CAGE-18-3 Cruise to the Barents Sea, Storfjorden Trough, East Greenland Ridge (Leg 1, 2), Arctic Ocean Vestnesa Ridge, and PKF, (Leg 3) - Rasmussen, Tine L.; Nielsen, Tove; Ofstad, Siri; Åström, Emmelie; El bani Altuna, Naima; Laier, Troels; Sen, Arunima; Chitkara, Cheshtaa; Frolova, Anastasiia; Mamadzhanian, Anna (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
From the evening of June 29th to the evening of July 10th 2018, CAGE at the Department of Geology Uit, the Arctic University of Norway, arranged a scientific cruise aimed at investigating methane seep sites by surface sediment sampling, sediment core sampling, plankton sampling and water sampling. The areas for investigation were the Barents Sea (Crater area), Storfjorden Trough (Pingo area),East Greenland Ridge (non-seep, for IODP-proposal) (Leg 1 and 2) and the western Svalbard margin, Vestnesa Ridge, Arctic Ocean and Prins Karls Forland (Leg 3) on R/V “Helmer Hanssen”. The scientific sampling was done within the framework of several ongoing projects at the Department of Geology, University of Tromsø: “CAGE -Centre for Arctic Gas Hydrate, Environment and Climate”-WP6: “Methane Release, Ocean Acidification and CO2” hereunder ocean acidification impact on marine calcifiers (planktic foraminifera and pteropods, methane seeping impact on ocean acidification and productivity, the state of the inorganic and organic biological pump from foraminifera, bottom water temperature change and impact on release of methane, living benthic microfauna studies from seep sites for geochemical investigations for calibrations for paleostudies. A total of 15 gravity cores (c. 60 m),and 31 CTD (conductivity-temperature-depth) casts were performed, 11 plankton net (no. 12 failed because the net was torn completely), 22 boxcore samples x 6 surface samples for each. A total of 137 lines of acoustics and seismics together were performed. Chirp profiles and multi-beam lines were acquired during transits and in surveys mapping of new seep sites northeast of “Crater” area, seep sites in Storfjorden Trough, East Greenland Ridge, seeps in Hinlopen trough and Norske Banken, the east slope of Yermak Plateau, active and inactive pockmarks at Vestnesa Ridge and a small patch off PKF for WP4. All acoustic and seismic investigations were performed with soft-start of all instruments (Echo-sounders, deep-penetrating echosounder (‘Chirp’), Multi-beam ...